Comparison of ultrasonic and photographic methods of axial length measurements of the eye. - Grey, R H (1977)
The axial length of 25 eyes was measured by the photographic method and by ultrasonography. The photographic measurements were consistently larger than the ultrasonic, but analysis gave a correlation coefficient of r = 0-8483. The results suggest that the centre of rotation of the eye lies posterior to the anatomical centre of the globe. Using an empirical method of calculation and allowing for an error of +/-0-3 mm in the ultrasonic measurement, the photographic results were within +/-0-5 mm in 13 eyes and +/-1-0 mm in 7 eyes. The photographic method may be helpful as a guide to the power of intraocular lens implants and for comparing axial lengths in population studies.